2012
DOI: 10.1164/rccm.201203-0478oc
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aspergillus fumigatus Infection on Vitamin D Receptor Expression in Cystic Fibrosis

Abstract: This study provides a rationale for the therapeutic effect of itraconazole and implied that the therapeutic potential of vitamin D supplementation in preventing ABPA is only feasible with concurrent elimination of A. fumigatus to permit VDR expression and its positive functional consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 37 publications
(43 reference statements)
0
60
1
Order By: Relevance
“…A. fumigatus polymerase chain reaction, a more sensitive method for its detection compared to culture alone, was positive in 70% of severe asthma with Aspergillus sensitization (SAAS) patients 40. Subgroup analysis revealed that A. fumigatus polymerase chain reaction became negative following treatment with itraconazole,40 a finding which was also illustrated in CF 39. Taken together, it is therefore plausible that antifungal therapy may be of benefit in patients with SAFS or SAAS; however, due to different methodologies in prior studies (including patient selection, duration of antifungal treatment and end points), strong conclusions cannot be drawn 4144…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A. fumigatus polymerase chain reaction, a more sensitive method for its detection compared to culture alone, was positive in 70% of severe asthma with Aspergillus sensitization (SAAS) patients 40. Subgroup analysis revealed that A. fumigatus polymerase chain reaction became negative following treatment with itraconazole,40 a finding which was also illustrated in CF 39. Taken together, it is therefore plausible that antifungal therapy may be of benefit in patients with SAFS or SAAS; however, due to different methodologies in prior studies (including patient selection, duration of antifungal treatment and end points), strong conclusions cannot be drawn 4144…”
Section: Discussionmentioning
confidence: 95%
“…There is a growing body of evidence to suggest a significant degree of airway colonization in patients sensitized to A. fumigatus ; however, importantly, colonization by this thermotolerant fungus is unrelated to its allergic manifestations 38,39. Importantly, ~60% of patients with moderate to severe asthma and IgE sensitization to A. fumigatus have positive sputum culture 7…”
Section: Discussionmentioning
confidence: 99%
“…Classifying patients into proposed subgroups and delineating those with ABPA from those who are AF sensitised, AF non-sensitised and those with aspergillus bronchitis [11]. Some studies have provided valuable insights into how AF may influence the progression of CF lung disease [9, 12, 13] however the true extent of the impact on disease progression is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous production of Th2 cytokines is concurrently promoted including IL-4, IL-5, and IL-10 in this setting [154, 162]. Our group and others have shown that elevated Th2 cytokine levels correlate with A. fumigatus positivity in people with CF (IL-5 and IL-13) and the development of IPA with particularly unfavorable outcomes in immunocompromised patients (IL-10) [70, 163]. In addition, Th2-associated cytokines suppress ROS production and hyphal damage of the fungi [164].…”
Section: Cytokines In the Innate Pulmonary Defense Against Aspergimentioning
confidence: 98%
“…Treatment with itraconazole decreases BAL gliotoxin concentrations, restoring VDR expression. Concurrently, a diminished systemic level of the Th2 cytokines IL-5 and IL-13 is detectable with concomitant improvement in clinical and radiological parameters [70]. Despite effective treatment options, an early diagnosis of ABPA with rapid initiation of therapy is key to prevent irreversible pulmonary damage irrespective of the underlying pulmonary condition [71].…”
Section: Allergic Bronchopulmonary Aspergillosis (Abpa)mentioning
confidence: 99%